Research on Spaceborne Multi-Beam Phased Array Fed Refl ector Antenna - Tao YANG; Lei LI; Yongqing ZOU (天地一体化信息网络)
Spaceborne multi-beam antenna is one of the main means to meet the needs of high-capacity and high-speed satellite communication services, and is widely used in various satellite communication systems.Various forms of antennas, such as spaceborne phased array multi-beam antenna, lens multi-beam antenna, conventional refl ector multi-beam antenna and phased array fed reflector multi-beam antenna were introduced.Here, a novel phased array fed reflector multi-beam antenna was demonstrated, the corresponding design method was given, and the prototype was developed and verifi ed.The proposed antenna has the characteristics of transmitting and receiving common aperture, small array size, low cost, scalable beam quantity, fast agility, high dynamic deployment effi ciency as well as good platform adaptability.Compared with the two-dimensional phased array antenna system, the antenna could achieved more beams.Compared with the multi-beam refl ector antenna, it could also realized the agility scanning of all beams and the centralized call ability of 93%~97%.